Kreativitas Guru PAI Dalam Melaksanakan Reinforcement Untuk Meningkatkan Motivasi Belajar Siswa di UPT SMP Negeri 23 Medan - Harahap, Febri Ali Karisma (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The research carried out entitled "Creativity of PAI Teachers in Implementing Reinforcement to Increase Student Learning Motivation at UPT SMP Negeri 23 Medan", aims to find out how creative PAI teachers are in implementing reinforcement to increase student learning motivation at UPT SMP Negeri 23 Medan and to find out the factors- factors that support and inhibit the creativity of pai teachers in implementing reinforcement to increase student learning motivation at UPT SMP Negeri 23 Medan. The research method used is qualitative research. Researchers used data collection techniques with observation, interviews and documentation. And the data analysis techniques used are data reduction, data presentation and drawing conclusions. Then to check the validity of the data, namely through triangulation. The results of research conducted at UPT SMP Negeri 23 Medan show that: (1) The creativity of pai teachers in carrying out reinforcement to increase student motivation at UPT SMP Negeri 23 Medan, that the teachers who were involved and became subjects and sources of data in this research have carry out reinforcement well, with various methods and creativity carried out by each of them, in different ways according to the thoughts of the teachers themselves. There are teachers who are more dominant in the form of punishment that deters students from their mistakes, and there are teachers who are more dominant in looking at students' backgrounds and taking a good approach and finding solutions for students who deviate from the concept of love, and there are also teachers who give forms of praise. and appreciation to students who excel.